Tax incentives for research - development activities by Vietnamese enterprises - Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Research and development (R&D) activities are very specific in their natures and then need to be encouraged and to get highest supports in incentive tax measures. Incentive tax measures, however, actually applied in Vietnam, for this specific sector of activities remain limited in many aspects. This study gives contributions to clarify the status, limited aspects of these tax incentives for R&D activities by Vietnamese enterprises and provides some suggestions for further consideration in the coming time. Code: 15081701